Analysis of Fundamental Algebraic Concepts and Information Security System - S M Nazmuz Sakib (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Cryptography plays a crucial role in protecting the data from unauthorized access. Nowadays, various cryptographic algorithms are used. It is not meant for information technology to secure the proposed work's primary target to achieve these tasks and goals. Using a literature review, we study security information systems using S-Boxes. In the research, we discuss two different techniques to generate the new S-boxes and then discuss their other properties to improve the strength of encryption. This chapter is further divided into sections that comprehensively explain the various concepts.